The choreography of belonging : toothed whale spatial cohesion and acoustic communication - Macfarlane, Nicholas Blair Wootton (Massachusetts Institute of Technology, 2016)
Thesis: Ph. D., Joint Program in Oceanography/Applied Ocean Science and Engineering (Massachusetts Institute of Technology, Department of Biology; and the Woods Hole Oceanographic Institution), 2016. Cataloged from PDF version of thesis. Includes bibliographical references. To maintain the benefits of group membership, social animals need mechanisms to stay together and reunite if separated. This thesis explores the acoustic signals that dolphins use to overcome this challenge and mediate their complex relationships in a dynamic 3D environment. Bottlenose dolphins are the most extensively studied toothed whale, but research on acoustic behavior has been limited by an inability to identify the vocalizing individual or measure inter-animal distances in the wild. This thesis resolves these problems by simultaneously deploying acoustic tags on closely-associated pairs of known animals. These first reported deployments of acoustic tags on dolphins allowed me to characterize temporal patterns of vocal behavior on an individual level, uncovering large variation in vocal rates and inter-call waiting time between animals. Looking more specifically at signature whistles, a type of call often linked to cohesion, I found that when one animal produced its own signature whistle, its partner was more likely to respond with its own whistle. To better evaluate potential cohesion functions for signature whistles, I then modeled the probability of an animal producing a signature whistle at different times during a temporary separation and reunion from its partner. These data suggest that dolphins use signature whistles to signal a motivation to reunite and to confirm identity prior to rejoining their partner. To examine how cohesion is maintained during separations that do not include whistles, I then investigated whether dolphins could keep track of their partners by passively listening to conspecific echolocation clicks. Using a multi-pronged approach, I demonstrated that the passive detection range of echolocation clicks ...